A reduced multiscale model for heat treatments in multiphase steels. (November 2016) - Barroqueiro, B.; Pinho-da-Cruz, J.; Dias-de-Oliveira, J.; Andrade-Campos, A.
Highlights: Prediction of the macrostructural behaviour of a multiphase steel subject to a heat treatment. Thermoelastic-viscoplasticity, anisotropy and phase transformations is accounted. The microstructure evolution and distribution is used to predict the overall response. The model allows a proper characterisation of the micro-macroscale without large DoF. Application of an AEH transient multiscale model to simulate heat treatments. Abstract: Multiphase steels offer impressive mechanical properties. However, their characterisation still represents a challenge. In a quenching processes, phenomena such as undesirable strains or residual stresses are inevitable and can be the cause for non-admissible final parts. In this work, a reduced multiscale model is proposed, being capable of accounting phenomena such as viscous effects and phase transformations. The existence of two distinct scales is assumed, defining a micro- and a macroscale. In the smaller scale, the evolution of a steel periodic microstructure is analysed in detail and Micro-Macro (M-M) instantaneous constitutive matrices are established for macroscopic use. These matrices are established using the asymptotic expansion homogenisation methodology, allowing to predict the macrostrutural response (macroscale) based on the microstructure (microscale) information.